CD93 as a Potential Target in Neovascular Age‐Related Macular Degeneration. Issue 7 (30th November 2016) - Tosi, Gian Marco; Caldi, Elena; Parolini, Barbara; Toti, Paolo; Neri, Giovanni; Nardi, Federica; Traversi, Claudio; Cevenini, Gabriele; Marigliani, Davide; Nuti, Elisabetta; Bacci, Tommaso; Galvagni, Federico; et al.
Abstract : In patients with age‐related macular degeneration (AMD), choroidal neovascularization is the major cause of severe visual loss. In these patients, the persistence of neovascular growth despite vascular endothelial growth factor‐A blockage needs the discovery of new endothelial cell targets. The glycoprotein CD93, highly expressed in activated endothelial cells, has been recently involved in the regulation of the angiogenic process both as transmembrane and soluble protein. Choroidal neovascular membranes from patients affected by AMD were examined by immunofluorescence using anti‐CD93 and anti‐von Willebrand factor antibodies. Blood vessels within intraocular and extraocular neoplasias were used as controls for CD93 expression. All choroidal neovascular membranes displayed strong CD93 staining in the von Willebrand factor‐positive endothelial cells, consistently with the analyses showing a high colocalization coefficient in the blood vessels. Intraocular and extraocular tumor vessels showed similar results, whereas the normal choroid displayed blood vessels with only faint CD93 staining. Additionally, the concentration of soluble CD93 was determined in the aqueous humor of patients affected by naïve neovascular AMD by enzyme‐linked immunosorbent assays. Age‐matched cataract patients served as controls. Soluble CD93 was significantly increased in the aqueous humor of naïve neovascular AMD patients and tended to decrease after treatment with an antiangiogenic drug. In conclusion, both transmembrane and soluble CD93 are overexpressed in patients with neovascular AMD, indicating that CD93 may represent a potential new antiangiogenic target in the treatment of choroidal neovascularization. J. Cell. Physiol. 232: 1767–1773, 2017. © 2016 Wiley Periodicals, Inc. Abstract : In patients with age‐related macular degeneration (AMD), the formation of new blood vessels in the choroid, which is the major cause of severe visual loss, persists even after therapy. In AMD patients, both in the endothelial cells of choroidal neovascular membranes and in the aqueous humor, we found high levels of the glycoprotein CD93, which has been recently involved in the enhancement of tumor vascular function. The presence of CD93 in AMD patients unveils a potential new target for choroidal neovascularization treatment.